Evangelicals and the philosophy of science - Mathieson, Stuart, author.
1 online resource.
Keywords: "This book investigates the debates around religion and science at the influential Victoria Institute. Founded in London in 1865, and largely drawn from the evangelical wing of the Church of England, it had as its prime objective the defence of 'the great truths revealed in Holy Scripture' from 'the opposition of science, falsely so called'. The conflict for them was not between science and religion directly, but rather what exactly constituted true science Chapters cover the Victoria Institute's formation, its heyday in the late Nineteenth Century, and its decline in the years following the First World War. They show that at stake was more than any particular theory; rather, it was an entire worldview, combining theology, epistemology, and philosophy of science. Therefore, instead of simply offering a survey of religious responses to evolutionary theory, this study demonstrates the complex relationship between science, evangelical religion, and society in the years after Darwin's Origin of Species. It also offers some insight as to why conservative evangelicals did not display the militancy of some American fundamentalists with whom they shared so many of their intellectual commitments. Filling in a significant gap in the literature around modern attitudes to religion and science, this book will be of keen interest to scholars of Religious Studies, the History of Religion, and Science and Religion"--